1999
DOI: 10.1007/s004230050229
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal sutureless anastomosis in pigs using absorbable intraluminal stents, stent placement devices, and fibrin glue - a summary

Abstract: The SAINT-PD has potential for all gastrointestinal sites, but needs larger experimental trials. The SS technique is impractical and had high tissue ridge formation and adhesion rates. These preliminary trials suggest the simplicity, versatility and safety of the SAINT technique; however, the small groups limit result interpretation. The results present a starting point for sutureless FG gastrointestinal anastomosis, and future experimental evaluation with more extensive statistical analyses in larger studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Thus, improvement of the anastomotic technique is a necessity. Non-suture colonic anastomosis has been the subject of many experiments [11][12][13][14][15][16][17]. Schafer et al [9] in a study on rabbits, demonstrated that suture-induced disturbances of the intestinal microcirculation lead to necrosis of the mucosa, partial and incomplete necrosis of the inverted cuff, and transmural necrosis with destruction of the sero-serous contact zone, leading to anastomotic leakage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, improvement of the anastomotic technique is a necessity. Non-suture colonic anastomosis has been the subject of many experiments [11][12][13][14][15][16][17]. Schafer et al [9] in a study on rabbits, demonstrated that suture-induced disturbances of the intestinal microcirculation lead to necrosis of the mucosa, partial and incomplete necrosis of the inverted cuff, and transmural necrosis with destruction of the sero-serous contact zone, leading to anastomotic leakage.…”
Section: Discussionmentioning
confidence: 99%
“…Kirkegaard et al [12] in an experimental study in rats found much more intestinal adhesions causing intestinal obstruction in the isobutylcyanoacrylate group. Detweiler et al [14] proposed the combination of absorbable intraluminal stents and fibrin glue in order to avoid adhesion formation and intestinal obstruction. Detweiler et al [14] proposed the combination of absorbable intraluminal stents and fibrin glue in order to avoid adhesion formation and intestinal obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…A sutureless anastomosis using fibrin glue is still in the experimental phase 33 and the laser, while capable of achieving union, may not (in animal experiments) produce a robust one 34…”
mentioning
confidence: 99%
“…In gastrointestinal tract surgery, there may be complications after anastomotic operations such as leaks, adhesions, stenosis and abscess formation at the anastomotic site [1,4,18,19,25]. In a pilot experiment, we made an incision in the colon and introduced about 2 cm of the ileum into the colonic lumen as described earlier.…”
Section: Discussionmentioning
confidence: 99%